THE ROLE OF ISLAMIC RELIGIOUS COUNSELORS IN THE PSYCHOLOGICAL REHABILITATION OF DRUG-ADDICTED FISHERMEN IN VILLAGE BANYAK ISLAND SUB-DISTRICT TANJUNG PURA - Muhammad Ihsan; Winda Kustiawan (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2023)
Drugs Already No is taboo and many people know about it danger as well as the resulting impact from usage drugs. However in fact user drugs moment This really high. this can happen Because not enough more knowledge and un derstanding deep about danger drugs from every circles public especially working people as fisherman. Study field (field research) with approach qualitative done to servant in Village Banyak Island sub-district Tanjung Pura for know role Islamic religious instructor in rehabilitation psychic fisherman addict drugs in Village Banyak Island sub-district Tanjung Pura. Research results showing that basically in method religious counseling in the community carried out by walking religious instructors Enough ok. As for the results implementation is Enough it worked, This proven with the more height awareness public Fishermen who think that Drugs no road go out for people who are frustrated and do not know the direction in his life. From several existing methods, more methods effective For do approach and able reveal problem in coaching base morals prisoner is method personal approach.